A Sunlight‐Induced Click Reaction as an Efficient Route to Cyclic Aliphatic Polyesters. Issue 11 (17th April 2015) - Josse, Thomas; De Winter, Julien; Altintas, Ozcan; Dubois, Philippe; Barner‐Kowollik, Christopher; Gerbaux, Pascal; Coulembier, Olivier
<x xml:space="preserve">Abstract</x> To date, the controlled preparation of cyclic polymers is mainly achieved using click ligation strategies. The light‐induced Diels–Alder click coupling has recently been shown to function as an attractive catalyst‐free alternative to the copper‐catalyzed alkyne–azide cycloaddition. However, the need for a light emitting system limits its applicability. To overcome this drawback, a sunlight‐induced Diels–Alder reaction as an efficient route for the preparation of cyclic aliphatic polyesters in high yields and purity based on the same chemistry is demonstrated in the present contribution. The versatility and robustness of the proposed strategy against divergent atmospheric conditions is demonstrated. In light of the simplicity of the strategy presented here, it is suggested that the sunlight‐induced Diels–Alder click‐cyclization is a world‐wide transposable process.